ANALISIS SWOT KEBUTUHAN KARYAWAN PERBANKAN SYARIAH DARI SARJANA EKONOMI SYARIAH IAIN PALANGKA RAYA - jelita, jelita; Wardana, Wilmar Okto (AL-QARDH, 2017)
This research background in IAIN Palangka Raya as one of the colleges that there is a container for printing human resources and potentional knowledgeable in the world of work. One of the graduate printed is a graduate of the Faculty of Economics and Business Islam with competence in the Islamic finance. But the facts on the ground are not little public data show that graduates become more dominant than the employees in Islamic banking scholars who really has the educational background of Islamic economics. The problem begins with the researcher tried to explore data about the SWOT analysis of the needs of potential economic scholars of sharia in Islamic banking city of Palangka Raya. The problem in this research are 1) Strength, 2) weakness, 3) opportunities, 4) the threats facing prospective Bachelor of Islamic Economics IAIN Palangka Raya on Islamic Banking city of Palangka Raya and 5) How can the application of a SWOT analysis in developing prospective Bachelor of Islamic Economics IAIN Palangka Raya Britain on Islamic Banking city of Palangka Raya.Â This study used qualitative research methods, the research subject is the faculty of economics and business of Islamic banking Islamic and 4 cities Palangka Raya ie BMI, BSM, BRIS and BPR Mitra Amanah. Data collection techniques through, observation, interviews and documentation; validating data through triangulation techniques, then the data analyzed by data reduction, a data display and conclusion verification.Â The results of this study are 1) The strength of a. have a basic knowledge of Islamic banking b. have a scholarly foundation related to Islamic financial institutions c. Output Islamic scholars who are experts in Islamic economics. 2) The weakness in terms of academic, SDM Teachers, curriculum learning, relationship. While the non-academic terms that mindset is still low degree candidate. 3) Opportunities have added value, priority religion, knowledge about Islamic banking contract-agreement, an understanding of the products; have communication skills and proficiency in a polite and courteous and knowledge in the field of Islamic religion. 4) Threats to the economy in the banking degree candidate is not looking at the educational background, dressed and physical conditions prescribed for frontline staff. 5) The results of a SWOT analysis required by prospective students of Islamic Economics Iain Palangka Raya on Islamic banking: a. Internal 1) Improving the teaching of human resources. 2) Development of the learning curriculum. 3) improve the relationship in the field of education. 4) Provide training in human resource development sharia economics degree candidate b. External Improvingstudent mindset to be able to develop themselves independent, creative, innovative and high work ethic.